STREAMING DATA OBJEK UNTUK PENGIRIMAN DATA PESAN DENGAN DUKUNGAN UML - K, Yuliana Rachmawati (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2006)
A job description of a programmer is to make problem solutions by developing a qualified software. The success of making software is based on good or bad design ma-de. Parameter of developing qualified software according to developer is easy to be de-signed, improved and reusable.This research discussed about the standard of modeling and designing software which was made by software designer. The result of this research showed that universal standard is needed in designing, especially related to software development and im-plementation. Good design not only showed object in detail but also not depend on soft-ware language used. UML is one of media to design software. Case study of streaming data object using UML, proved that design standard is needed for developer to make implementation ea-sier.